Three-dimensional STED microscopy of aberrating tissue using dual adaptive optics - Patton, B; Booth, M; Owald, D; Burke, D; Gould, T; Bewersdorf, J (Optical Society of America, 2016)
When imaging through tissue, the optical inhomogeneities of the sample generate aberrations that can prevent effective Stimulated Emission Depletion (STED) imaging. This is particularly problematic for 3D-enhanced STED. We present here an adaptive optics implementation that incorporates two adaptive optic elements to enable correction in all beam paths, allowing performance improvement in thick tissue samples. We use this to demonstrate 3D STED imaging of complex structures in Drosophila melanogaster brains.